1996
DOI: 10.1063/1.116216
|View full text |Cite
|
Sign up to set email alerts
|

Microcontact printing and pattern transfer using trichlorosilanes on oxide substrates

Abstract: Microcontact printing was used to pattern silicon, aluminum, and titanium substrates using octadecyltrichlorosilane as the ink and an elastomer as the stamp. Patterns were transferred into the substrates using both dry and wet etching. The Al and Ti were etched using an electron cyclotron resonance (ECR) plasma source at low ion energies and low pressure. Silicon was etched in HF to remove the native oxide, followed by KOH. Microcontact printing using OTS ink is a convenient and easy way to pattern both semico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 4 publications
0
43
0
1
Order By: Relevance
“…Printed patterns have been transferred from Au to semiconductors such as Si [14] and GaAs [15] by reactive ion etching, and Si has been patterned directly using siloxane SAMs on Si-OH surfaces [16] or alkoxyl SAMs on Si-Cl surfaces [17]. Siloxane SAMs have been used to pattern SiO 2 [18], trichlorosilane SAMs to pattern oxides such as Al 2 O 3 and TiO 2 [19] and alkanephosphonic acids to pattern ITO [20]. Reviews of ink/substrate combinations can be found in [21,22], and there is interest in inks that are less specific to particular substrates [23].…”
Section: Introductionmentioning
confidence: 99%
“…Printed patterns have been transferred from Au to semiconductors such as Si [14] and GaAs [15] by reactive ion etching, and Si has been patterned directly using siloxane SAMs on Si-OH surfaces [16] or alkoxyl SAMs on Si-Cl surfaces [17]. Siloxane SAMs have been used to pattern SiO 2 [18], trichlorosilane SAMs to pattern oxides such as Al 2 O 3 and TiO 2 [19] and alkanephosphonic acids to pattern ITO [20]. Reviews of ink/substrate combinations can be found in [21,22], and there is interest in inks that are less specific to particular substrates [23].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional metal deposition techniques such as evaporation, sputtering, and chemical vapor deposition bring considerable energy to the surface during the deposition process and are known to damage the surface molecular layer 271,272 and result in metalorganic interfaces with inconsistent, inhomogeneous, and leaky electrical conducting properties. 273,274 To minimize the impact of the metallization process, "soft" techniques, such as indirect deposition, [275][276][277] nano-particles deposition, [278][279][280] electrochemical methods, [281][282][283] "lift-off float-on (LOFO)," 284,285 mercury droplet contacts, 286,287 micro-contact printing, [288][289][290][291] have been specially designed and implemented to achieve more consistent results. The effect of a molecular layer on the SBH is found to be less consistent and predictable than its effect on the surface potential of the semiconductor or the metal.…”
Section: Dv¼mentioning
confidence: 99%
“…Ein Schlüsselschritt ist im Allgemeinen die räumlich differenzierte Selbstorganisation von Monoschichten auf dem Substrat 8. Von den vielen bislang untersuchten Systemen fanden nur auf Siliciumdioxid selbstorganisierte Siloxane9 sowie auf Gold selbstorganisierte Alkanthiolate10 weitere Anwendung. Biomedizinische Produkte werden jedoch nur in den seltensten Fällen aus Silicium oder Gold hergestellt, meist werden Polymere sowie andere Metalle verwendet.…”
Section: Methodsunclassified